Analysis of gene expression and use of connectivity mapping to identify drugs for treatment of human glomerulopathies - Chung, Chen-Fang; Papillon, Joan; Navarro-Betancourt, José R.; Guillemette, Julie; Bhope, Ameya; Emad, Amin; Cybulsky, Andrey V. (Frontiers in Medicine, 2023)
Background: Human glomerulonephritis (GN) – membranous nephropathy (MN), focal segmental glomerulosclerosis (FSGS) and IgA nephropathy (IgAN), as well as diabetic nephropathy (DN) are leading causes of chronic kidney disease. In these glomerulopathies, distinct stimuli disrupt metabolic pathways in glomerular cells. Other pathways, including the endoplasmic reticulum (ER) unfolded protein response (UPR) and autophagy, are activated in parallel to attenuate cell injury or promote repair. Methods: We used publicly available datasets to examine gene transcriptional pathways in glomeruli of human GN and DN and to identify drugs. Results: We demonstrate that there are many common genes upregulated in MN, FSGS, IgAN and DN. Furthermore, these glomerulopathies were associated with increased expression of ER/UPR and autophagy genes, a significant number of which were shared. Several candidate drugs for treatment of glomerulopathies were identified by relating gene expression signatures of distinct drugs in cell culture with the ER/UPR and autophagy genes upregulated in the glomerulopathies (“connectivity mapping”). Using a glomerular cell culture assay that correlates with glomerular damage in vivo, we showed that one candidate drug – neratinib (an epidermal growth factor receptor inhibitor) is cytoprotective. Conclusion: The UPR and autophagy are activated in multiple types of glomerular injury. Connectivity mapping identified candidate drugs that shared common signatures with ER/UPR and autophagy genes upregulated in glomerulopathies, and one of these drugs attenuated injury of glomerular cells. The present study opens the possibility for modulating the UPR or autophagy pharmacologically as therapy for GN.